2012
DOI: 10.1080/02646838.2012.693153
|View full text |Cite
|
Sign up to set email alerts
|

Going back to work after childbirth: women’s lived experiences

Abstract: Objective: The study aimed at understanding the experiences of first-time mothers who returned to work after paid maternity leave. It explored the challenges new mothers faced during the transition of having a baby, taking 14 weeks of paid maternity leave and then returning to work. Background: Traditionally women left paid employment and stayed at home while their children were still young, but recent times have seen a change in local women's labour force participation and the actual lived experiences of Malt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 20 publications
2
20
0
5
Order By: Relevance
“…Se as suas famílias fossem nanceiramente mais abastadas teriam optado por car em casa com o bebé, aspiração igualmente partilhada por muitas outras mães trabalhadoras (Nichols & Roux, 2004;Spiteri & Xuereb, 2012). A articulação entre estes dois polos identitários fez também emergir a tensão característica dessa conciliação (Lipovetsky, 2007;Martins, 2012).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Se as suas famílias fossem nanceiramente mais abastadas teriam optado por car em casa com o bebé, aspiração igualmente partilhada por muitas outras mães trabalhadoras (Nichols & Roux, 2004;Spiteri & Xuereb, 2012). A articulação entre estes dois polos identitários fez também emergir a tensão característica dessa conciliação (Lipovetsky, 2007;Martins, 2012).…”
Section: Discussionunclassified
“…Porque as mulheres continuam a ser as principais cuidadoras (Martins, Abreu, e Figueiredo, 2014;Pinquart & Teubert, 2010), são geralmente as mulheres que mais desinvestem pro ssionalmente para gerir os múltiplos papéis e é também consensual em Portugal que, em caso de incompatibilidade ou di culdades na conciliação, a abdicação da carreira seja feminina (Aboim, 2010). O corpo de conhecimento que descreve a experiência vivida pelas mães no regresso ao trabalho após a licença parental é, no entanto, escasso (Nichols & Roux, 2004;Spiteri & Xuereb, 2012). Este estudo pretende explorar sentimentos e experiências de mães que regressam ao trabalho durante os primeiros seis meses de vida da criança e surge em complementaridade a um outro artigo que desocultou as estratégias utlizadas na conciliação do papel parental com o de trabalhador (Martins, 2012).…”
Section: Introductionunclassified
“…Evaluating data from a large mixed‐method descriptive study these researchers identified that role conflict/overload, family stress, family/child issues, financial issues, and psychosocial issues presented challenges to adjustment upon returning to work. Spiteri and Xuereb () in a study conducted in Malta focused on the new mothers’ thoughts after returning to work. These authors found that women were unprepared for life changes associated with having a baby and returning to work.…”
Section: Psychosocial and Social Supportmentioning
confidence: 99%
“…Indeed, research has demonstrated mothers are likely to experience a 'weathering of the storm' on returning to work, in an attempt to balance work and family life [17], relying on other working mothers for support and resocialisation [10]. Academic research is not necessarily keeping pace with organizational practice, as organizations such as Deloitte and Shell are now developing programmes to support women transitioning through parenthood in the form of coaching programmes.…”
mentioning
confidence: 99%